Pyogenic Granuloma - A Case Report - Sadiq, Safat; Ramesh, Amitha; Bhandary, Rahul; Shetty, Priyanka (Journal of Health and Allied Sciences NU, 2016)
Pyogenic Granuloma is a relatively common mucocutaneous lesion seen in the oral cavity, as a response to some underlying local irritant. This condition is frequently associated with periodontal pain and discomfort, and in some cases interferes with mastication and aesthetic problems. This paper presents a case of pyogenic granuloma managed by surgical intervention.
Keywords: Granuloma pyogenicum; hyperplastic lesion; granuloma